Combined experimental- and FE-studies on sinter-Ag behaviour and effects on IGBT-module reliability - Dudek, R.; Doring, R.; Sommer, P.; Seiler, B.; Kreyssig, K.; Walter, H.; Becker, M.; Gunther, M. (EuroSimE : 2014 15th International Conference on Thermal, Mechanical and Mulit-Physics Simulation and Experiments in Microelectronics and Microsystems : 7-9 April 2014, 2014)
For high temperature interconnection sintered silver can be used, however, it induces new demands on the thermo-mechanical design. That issue requires knowledge on the thermo-mechanical reliability of silver sintered devices, the subject of this paper. Material characteristics of the sinter layers are needed for simulation, which are addressed in the first part of the paper. Based on material properties of pure silver, for sintered silver with different porosities effective material characteristics have been derived by use of a micromechanical cell model. Shear loadings with in-situ deformation analyses have also been made to investigate sintered silver behavior. A complicated dependence on processing, temperature, and deformation rate is seen. Based on different effective constitutive models for the sintered interconnects, stress loadings are studied for a power module, an IGBT on DCB substrate, for passive and active thermal cycling. For the passive cycle complex interactions of the different layers of the stack are observed, which are not seen in a module with soft solder bonding. This result can be attributed to the missing decoupling by the soft soldering layer. Failure risks are evaluated by both conventional FEA and cohesive zone modeling. A quite different stress situation is depicted for active power cycling. The situation is even more complex and it is obvious from the simulations, that active power cycling can induce failure modes different from passive cycling.